Family communication challenges of adolescents and young adults with Li-Fraumeni syndrome: Implications for psychosocial care. Issue 11 (November 2022) - Rising, Camella J.; Wilsnack, Catherine; Boyd, Patrick; Sleight, Alix G.; Hutson, Sadie P.; Khincha, Payal P.; Werner-Lin, Allison
Abstract: Objectives: This qualitative-descriptive study explored adolescent and young adult (AYA) perspectives, experiences, and challenges with openness and closedness in family communication about Li-Fraumeni syndrome (LFS). Methods: We conducted interviews with AYAs (aged 15–39 years) with LFS enrolled in the National Cancer Institute's LFS study (NCT01443468). An interprofessional clinician-researcher team analyzed transcribed data using the constant comparative method and interpretive description. Results: AYAs ( N  = 38; 26 females, 12 males, mean age=29 years) reported navigating openness and closedness about LFS in their families, which varied by LFS topic, relationship, disease trajectory, and developmental phase. AYAs described communication challenges, including broaching difficult topics (e.g., reproductive decision-making, end-of-life), balancing information-sharing with emotionally protecting family and self, and struggling with interactions that cause relational tensions. Conclusions: AYAs reported experiencing LFS family communication challenges that disrupted their psychosocial well-being. LFS-related stressors and life transitions complicated and were complicated by these challenging family interactions. Practice implications: Clinicians may support AYAs with LFS by inquiring about family communication, responding empathically to communication concerns, providing resources to support difficult conversations, and engaging mental health providers as needed. Researchers could partner with AYAs to develop tailored communication skills training and social support tools. Highlights: AYAs reported complex syndrome-related family communication despite openness. AYAs balanced information-sharing with emotionally protecting family and self. AYAs linked closedness with sensitive and tension-inducing topics (e.g., family formation). Syndrome-related family communication challenged participants' mental health. Mental health referrals may be needed to support family communication and skill-building.